Pengaruh Harga, Promosi Dan Event Marketing Terhadap Keputusan Pembelian : Studi pada Konsumen Erigo di Jakarta Barat - Salsabillah, Avifah; Vildayanti, Rina Ayu (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of price, promotion, and event marketing on consumer purchasing decisions for Erigo products in West Jakarta. In the increasingly competitive fashion industry, companies are required to design effective marketing strategies to attract consumer interest and improve purchasing decisions. This research employed a quantitative approach using a survey method. The research sample consisted of 100 respondents who were consumers of Erigo products in the West Jakarta area. The sampling technique used was non-probability sampling with an accidental sampling method. Data collection was carried out through questionnaires distributed to respondents using a Likert scale to measure their perceptions of the research variables. The collected data were then processed and analyzed using SPSS version 26 through descriptive statistical analysis and hypothesis testing. The results of the study indicate that price, promotion, and event marketing have a significant influence on consumer purchasing decisions. These findings suggest that appropriate pricing strategies, effective promotional activities, and attractive event marketing programs can increase consumer interest and influence purchasing decisions for Erigo products. This study is expected to provide valuable insights for companies in developing more effective marketing strategies to enhance competitiveness and strengthen brand positioning in the market.